Percutaneous coronary intervention in patients with acute coronary syndrome: focus on bivalirudin - Ravi K Ramana; Bruce E Lewis (Vascular Health and Risk Management, 2008)
Ravi K Ramana, Bruce E LewisDivision of Cardiology, Loyola University Medical Center, Maywood, Illinois, USAAbstract: Previously, indirect thrombin inhibitors such as unfractionated heparin or low-molecular-weight heparin were used as a standard anticoagulation during percutaneous coronary intervention to prevent procedural thrombotic complications but at a risk of hemorrhagic complications. More recently, bivalirudin, a member of the direct thrombin inhibitor class, has been shown to have 1) predictable pharmacokinetics, 2) ability to inhibit free- and clot-bound thrombin, 3) no properties of platelet activation, 4) avoidance of heparin-induced thrombocytopenia, and 5) a significant reduction of bleeding without a reduction in thrombotic or ischemic endpoints compared to heparin and glycoprotein IIbIIIa inhibitors when used in patients presenting with acute coronary syndrome who are planned for an invasive treatment strategy.Keywords: bivalirudin, coronary intervention, direct thrombin inhibitor, acute coronary syndrome